Response of floral hemp production to fertilizer nitrogen and phosphorus rates - Tina Sullivan; Matt Yost; Dakota Boren; Earl Creech; Grant Cardon; Bruce Bugbee (Agrosystems, Geosciences & Environment)
Abstract Few studies have evaluated the fertilizer requirements of floral hemp (Cannabis sativa L.). When hemp production was first legalized in Utah in 2019, many growers had questions about fertilizer requirements. Some crop consultants were advising growers that hemp required extremely high N and P rates for optimal production. The objective of this study was to evaluate N and P requirements of outdoor irrigated floral hemp production in the Intermountain West. A field study was established in 2020 near Logan, UT, replicated in 2021, and expanded in 2022. In 2020–2021, three treatments included a control (university fertilizer guidelines for corn [Zea mays L.] given no reference for hemp) and 112 kg N ha−1 or 112 kg P2O5 ha−1 above the control. The 2022 trial was expanded to include five fertilizer N levels, four fertilizer P levels, and a nonfertilized control. Female Trump hemp clones were transplanted in late May and harvested in September and October in all years. The results from 2020–2021 showed no harvest index (leaf and flower biomass: total aboveground biomass), biomass yield, stem yield, and cannabinoid concentration increases due to N or P above the recommended rates for corn. The results from 2022 were similar, and the nonfertilized control had the same oil and floral yield as all fertilized treatments. Collective interpretation indicates that hemp does not require more applied inorganic N or P than recommendations for corn and that fertilizer responsiveness may be limited. Further, excessively high N and P fertilizer rates should not be recommended for outdoor hemp.